Analisis Pendekatan Struktural Pada Puisi Berjudul “SILHUET” Karya Taufiq Ismail - Wayan Tiadilona; Munaris Munaris; Heru Prasetyo (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Poetry is one of the literary genres written in a beautiful and rhythmic language, using words full of meaning and emotions. The purpose of this research is to analyze Taufiq Ismail's poem "Silhuet" using a structural approach, as poetry has a dominant aesthetic function and carries beautiful meanings. This research uses a descriptive qualitative method with a structural approach and data collection techniques such as reading and note-taking. The results of this research are the overall physical and inner structures in Taufiq Ismail's poem "Silhuet." The physical structure analyzed includes the form of the poem, diction, concrete words, language style, and imagery, while the inner structure analyzed includes the theme, tone, mood, and message.